Applications of Stochastic Optimal Control to Economics and Finance - Federico, Salvatore; Ferrari, Giorgio; Regis, Luca; Federico, Salvatore; Ferrari, Giorgio; Regis, Luca (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In a world dominated by uncertainty, modeling and understanding the optimal behavior of agents is of the utmost importance. Many problems in economics, finance, and actuarial science naturally require decision makers to undertake choices in stochastic environments. Examples include optimal individual consumption and retirement choices, optimal management of portfolios and risk, hedging, optimal timing issues in pricing American options, and investment decisions. Stochastic control theory provides the methods and results to tackle all such problems. This book is a collection of the papers published in the Special Issue (3z(BApplications of Stochastic Optimal Control to Economics and Finance(3y(B, which appeared in the open access journal Risks in 2019. It contains seven peer-reviewed papers dealing with stochastic control models motivated by important questions in economics and finance. Each model is rigorously mathematically funded and treated, and the numerical methods are employed to derive the optimal solution. The topics of the book$1 (Bs chapters range from optimal public debt management to optimal reinsurance, real options in energy markets, and optimal portfolio choice in partial and complete information settings. From a mathematical point of view, techniques and arguments of dynamic programming theory, filtering theory, optimal stopping, one-dimensional diffusions and multi-dimensional jump processes are used.s
English
Keywords: Economics, finance, business & management; debt crisis; government debt management; optimal government debt ceiling; government debt ratio; stochastic control; decision analysis; risk management; Bayesian learning; Markowitz problem; optimal portfolio; portfolio selection; Markov additive processes; Markov regime switching market; Markovian jump securities; asymptotic arbitrage; complete market; multiple optimal stopping; general diffusion; real option analysis; energy imbalance market; optimal reinsurance; excess-of-loss reinsurance; Hamilton-Jacobi-Bellman equation; stochastic factor model; American options; least square method; derivatives pricing; binomial tree; stochastic interest rates; quadrinomial tree; insurance; unemployment; optimal stopping; geometric Brownian motion; martingale; free boundary problem; American call option; utility